PENGARUH PENURUNAN TARIF PAJAK PPH FINAL DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KABUPATEN REMBANG - Widodo, Agus (JAB (Jurnal Akuntansi & Bisnis), 2019)
This study was conducted to determine the effect of reducing the final PPh tariff and tax sanctions on MSME taxpayer compliance. The technique of taking data collection is done by surveying techniques by distributing questionnaires that contain a list of questions directly to MSMEs that fulfill the sampling requirements. The sample population used in this study were 115 respondents who have registered as taxpayers. The results of this study indicate that the variable Tax Tariff Reduction (X1) has a T count> Table that is 13,337> 1.98157. This shows that the Tax Compliance at UMKM in Rembang Regency is strongly influenced by the policy that has been issued by the government in terms of reducing the PPh tariff for MSMEs, namely the 1% tariff reduction stated in PP 46 of 2013 to 0.5% in PP 23 of 2018. With the PPh Tariff Reduction policy, it increases Tax Compliance at MSMEs in Rembang Regency. Based on partial hypothesis testing (T test) shows that the variable Tax Sanctions (X2) has a T count> Table that is 3,764> 1.98157. This shows that Tax Compliance at MSMEs in Rembang Regency is strongly influenced by Tax Sanctions. With the Tax Sanction, it is expected that UMKM Taxpayers in Rembang Regency can fulfill their tax obligations obediently. From the test above, it is obtained that Tax Sanctions can increase Tax Compliance in UMKM Taxpayers in Rembang Regency. The conclusion of this study is that the dependent variable that is tax compliance is influenced by the independent variable namely the reduction of the final PPh tax rate for MSMEs and tax sanctions. This research is expected to increase the awareness of MSME taxpayers who are in the Rembang regency in fulfilling their obligations as taxpayers.Â Keyword: MSMEs, Tariff Reductions, Tax Sanctions, Tax Compliance